Evaluating the Stress Response as a Bioindicator of SubLethal Effects of Crude Oil Exposure in Wild House Sparrows (Passer domesticus). - Romero, L. Michael.; Lattin, Christine R.; Ngai, Heather M. (Tufts University. Tisch Library., 2016)
Petroleum can disrupt endocrine function in humans and wildlife, and interacts in particularly complex ways with the hypothalamus-pituitary-adrenal (HPA) axis, responsible for the release of the stress hormones corticosterone and cortisol (hereafter CORT) Ingested petroleum can act in an additive fashion with other stressors to cause increased mortality, but it is not clear exactly why—does petroleum disrupt feedback mechanisms, stress hormone production, or both? This laboratory study aimed to quantify the effects of ingested Gulf of Mexico crude oil on the physiological stress response of house sparrows (Passer domesticus) We examined baseline and stress-induced CORT, negative feedback, and adrenal sensitivity in house sparrows given a 1% oil or control diet (n = 12 in each group) We found that four weeks on a 1% oil diet did not alter baseline CORT titers or efficacy of negative feedback, but significantly reduced sparrows' ability to secrete CORT in response to a standardized stressor and adrenocorticotropin hormone injection, suggesting that oil damages the steroid-synthesizing cells of the adrenal. In another group of animals on the same 1% oil (n = 9) or control diets (n = 8), we examined concentrations of eight different blood chemistry parameters, and CORT in feathers grown before and during the feeding experiments as other potential biomarkers of oil exposure. None of the blood chemistry parameters differed between birds on the oil and control diets after two or four weeks of feeding, nor did feather CORT differ between the two groups. Overall, this study suggests that the response of CORT to stressors, but not baseline HPA function, may be a particularly sensitive bioindicator of sub-lethal chronic effects of crude oil exposure.